Analisa Kelayakan Usaha Purse Seine pada KM Bintang Bahagia 6 di Pelabuhan Umum Benoa, Provinsi bali - Maria Angelina Vicario Tonga; I Wayan Restu; I Ketut Wija Negara (Program Studi Manajemen Sumberdaya Perairan, Fakultas Kelautan dan Perikanan, Universitas Udayana, 2020)
This study objectives is to determine how the condition of the purse seine fishery business and also to determine the feasibility of the purse seine fisheries business in Benoa Public Port. In this study the method used is descriptive quantitative method. The data analysis method used is by calculating income, depreciation, and business profits, then to find out the business feasibility calculated the value of the payback period, B / C ratio, break event point. The primary data taken is data belonging to KM Bintang Bahagia 6 which is in the form of fish catch data per trip for 1 year, investment costs, fixed costs and variable costs, while secondary data is taken from the literature as well as data from the Directorate General of Marine Resources and Fisheries in the form of data on the number of purse seine fleets and the number of catches of purse seine vessels in Benoa Public Port. The condition of the fisheries business with purse seine fishing equipment in Benoa Public Port can be categorized as still quite good. This can be seen from the large number of operating fleets and the catches obtained are still relatively stable. The value of the payback period obtained is 1.1, B / C ratio 1.6, and BEP units of 99,433 kg and BEP sales of Rp 2,165,557,791. With this analysis, it can be stated that purse seine fisheries are feasible.